2020
DOI: 10.1177/0269215520968694
|View full text |Cite
|
Sign up to set email alerts
|

Addition of aerobic training to conventional rehabilitation after hip fracture: a randomized, controlled, pilot feasibility study

Abstract: Objectives: To determine the feasibility and safety of aerobic training with an arm crank ergometer and its effectiveness in improving functional capacity and gait in patients with recent hip fracture. Design: Randomized, controlled, assessor-blinded pilot study, with intention-to-treat analysis. Setting: Inpatients, rehabilitation department. Subjects: 40 patients with hip fracture surgically treated. Interventions: Training group performed aerobic exercise with an arm crank ergometer (15 sessions, 30 minutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…However, more repetitions of the 30 s STS in both groups at follow-up were still below the normative value for 70 years old elderly [ 65 ]. These results are in line with our previous study [ 33 ]. Notably, in patients with recent femur fractures, aerobic training with an arm crank ergometer did not result in a greater improvement in performance compared with those who underwent only standard rehabilitation and did not reach the normal range in the brief rehabilitative period.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…However, more repetitions of the 30 s STS in both groups at follow-up were still below the normative value for 70 years old elderly [ 65 ]. These results are in line with our previous study [ 33 ]. Notably, in patients with recent femur fractures, aerobic training with an arm crank ergometer did not result in a greater improvement in performance compared with those who underwent only standard rehabilitation and did not reach the normal range in the brief rehabilitative period.…”
Section: Discussionsupporting
confidence: 94%
“…The addition of aerobic exercise performed with an arm crank ergometer appears to be beneficial for people with subacute COVID-19. Previous studies have reported that arm aerobic exercise can be an effective training modality among healthy older people and patients with hip fractures, peripheral arterial disease, and post-stroke [ 33 , 59 , 60 , 61 ]. The benefits gained regard not only the cardiovascular function but also the physical functional performance, such as walking, balance, mobility, and motor acquisition since several lines of evidence suggested that a single bout of moderate-intensity aerobic exercise may also be enough [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These consequences last months after surgery, with 50% experiencing reduced functionality within one year, while only 30% regain full functionality [15]. Exercise has significant benefits for several of these variables, such as the level of independence and self-care [16,17], the faster clearance of accumulated lactate [18,19], the increased activity of pyruvate dehydrogenase [20] and the immediate enhancement of cognitive functions [21]. Hemostasis is also linked to exercise physiology, as it affects blood coagulation, fibrinolysis and platelets [22].…”
Section: Introductionmentioning
confidence: 99%